2019
DOI: 10.21926/obm.neurobiol.1903035
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Periostin in Brain Injury Caused by Subarachnoid Hemorrhage

Abstract: Aneurysmal subarachnoid hemorrhage (aSAH) causes serious brain injury, and its mechanisms have not been completely unraveled so far. The causative factors for the brain injury initiated by an aneurysm rupture, which is referred to as the early brain injury (EBI), include elevated intracranial pressure, cerebral hypoperfusion, and blood contents that are directly exposed to the brain surface. At Day 4-14 post aSAH, delayed cerebral ischemia (DCI) often develops, which may worsen the neurological outcomes critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Recently, machine learning analyses have been developed and constructed early prediction models for the occurrence of DCI, angiographic cerebrovascular spasm, and delayed cerebral infarct using admission clinical factors and plasma levels of three types of matricellular proteins (OPN-a, periostin, and galectin-3) at post-SAH days one to three in a clinical setting [35]. Periostin and galectin-3 have been implicated in EBI and DCI or delayed cerebral infarction after SAH [36][37][38][39][40][41][42][43][44]. However, a clinical study demonstrated that plasma OPN-a levels at days one to three were also one of the three most important features in all of the three prediction models with high accuracy and sensitivity [35].…”
Section: Role As a Biomarkermentioning
confidence: 99%
“…Recently, machine learning analyses have been developed and constructed early prediction models for the occurrence of DCI, angiographic cerebrovascular spasm, and delayed cerebral infarct using admission clinical factors and plasma levels of three types of matricellular proteins (OPN-a, periostin, and galectin-3) at post-SAH days one to three in a clinical setting [35]. Periostin and galectin-3 have been implicated in EBI and DCI or delayed cerebral infarction after SAH [36][37][38][39][40][41][42][43][44]. However, a clinical study demonstrated that plasma OPN-a levels at days one to three were also one of the three most important features in all of the three prediction models with high accuracy and sensitivity [35].…”
Section: Role As a Biomarkermentioning
confidence: 99%
“…Periostin is a 90-kDa matricellular protein which is a kind of non-structural, inducible, and multifunctional extracellular matrix protein [1]. In a normal condition, periostin exists at low levels in adult tissues and is upregulated in an injured or inflamed tissue [1,30]. Our previous studies reported that plasma periostin was increased in an acute phase of aneurysmal SAH in clinical settings [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Subarachnoid hemorrhage (SAH) remains a poor-outcome cerebrovascular disorder and is associated with secondary neurological disorders and brain damages that proceed after its onset [1,2]. Early brain injury (EBI) is considered to be the main cause of poor outcomes, and begins to occur immediately after aneurysmal rupture, which triggers elevation of intracranial pressure and thereby global cerebral hypoperfusion and ischemia, as well as spreading of blood components into the subarachnoid space [3].…”
Section: Introductionmentioning
confidence: 99%